1994
DOI: 10.1016/0885-3924(94)90146-5
|View full text |Cite
|
Sign up to set email alerts
|

Delirium as a contributing factor to “crescendo” pain: Three case reports

Abstract: Cancer patients occasionally experience periods of rapidly escalating pain--"crescendo" pain--that may present a challenge in assessment and management. Although these episodes are often associated with progressive neoplasm, any of a variety of other processes may be involved. Delirium is a potentially treatable and frequently unrecognized factor. We present three patients who illustrate this relationship between delirium and a crescendo pattern of cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…45,46 When one or more of these components is unclear, a physician specialist, with relevant expertise and experience, should be consulted to clarify the assessment.…”
Section: Assessmentmentioning
confidence: 99%
“…45,46 When one or more of these components is unclear, a physician specialist, with relevant expertise and experience, should be consulted to clarify the assessment.…”
Section: Assessmentmentioning
confidence: 99%
“…Specifically, many surveys have demonstrated that opioid doses typically stabilize during long term administration (17,24,62,(64)(65)(66)69,99,(109)(110)(111)(112)(113). When the need for dose escalation occurs, it is usually readily explained by a worsening physical lesion (24,114) or a changing psychological state (115). Analgesic tolerance, therefore, seldom compromises the efficacy of therapy, and concern about tolerance does not justify a decision to withhold or delay a therapeutic opioid trial.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…1 Delirium in patients with cancer has been associated with adverse outcomes, including decreased performance status 2 ; increased pain and use of breakthrough analgesia 3,4 ; longer length of hospital stay 5,6 ; increased distress for the patient, spouse, caregivers, and nurses [7][8][9] ; and decreased survival.…”
Section: Introductionmentioning
confidence: 99%